Commercial organisations head’s innovative competencies model - M. S. Blokhina (Цифровая социология, 2022)
Digitalisation and the innovative economy have generated many social processes and transformations, and set many tasks. These changes were especially clearly reflected in the professional activities of the commercial sector heads. Today, they can no longer perform their duties effectively, having only general cultural and professional competencies in their portfolio. The formation of different, new type competencies is required. However, we are not talking about disparate, separate skills and abilities, the sporadic description of which is found in professional standards or requirements for vacancies in the positions of top managers. There is a need for the formation and development of competencies among the heads of commercial organisations responsible for the birth of innovations and involvement in the processes of the innovative economy. Sociological researchers are faced with the tasks of defining this concept, detailed description of innovative competences, their distinctive features from competences of other types, systematization and grouping. The article presents the author’s model of innovative competencies obtained as a result of sociological research “The role of innovative competencies in professional activity of managers of commercial organisations”. The model can serve as a basis for further research in this field and development of this direction of sociology.